Uso de SIG para identificar áreas suscetíveis a deslizamentos e desmoronamentos : aplicação nas favelas da Serra de Santa Teresa, cidade do Rio de Janeiro - Guimarães, Ladjane Marques (2004)
The big unbalanced social and living conditions in Rio de Janeiro were responsible for sprouting of slums since the end of XIX century. As a consequence of deforestation in the hillsides the slopes became unstable generating occurrence of land slide, material and life loses. This work aimed to study the hillsides of Santa Teresa (RJ) neighborhood, located in the abutments of the Tijuca mountain range. The proximity to the sea promotes occurrence of relief rains of great intensity. Taking into account that the mountains are of biotitic gneiss, composed of unstable iron magnesian minerals, the area becomes very prone to land slide, especially on steeper hillsides occupied by precarious habitations of low income population. A graphical and a non-graphical data base for the area was constructed using geo-processing techniques and Geographical Information System. Results of crossing this data with IBGE demographics and social data indicates that 77,6% of the slum area occurs in areas of mass movement risk. The slum in risk areas related to its domiciliary mean density indicates that 75,5% of the population lives in high risk situation.